Growth hormone-releasing peptide and its analogues Novel stimuli to growth hormone release. - Korbonits, M; Grossman, AB (1995)
GHRPs are oligopeptides with GH-releasing effects in humans when given by either parenteral or oral routes; in addition, nonpeptide pharmacologic analogues have recently been synthesized. Although the exact mechanism of action of these agents has not been fully established, there is probably a dual site of action on both the pituitary and the hypothalamus, possibly involving regulatory factors in addition to GHRH and somatostatin. GHRPs and their analogues may have a potential role in the treatment of short stature in children or in other situations of GH deficiency, such as adult GH deficiency, obesity, catabolic states, and even normal old age.